Pengembangan Aspek Motorik AUD Melalui Permainan Englek - Khadijah Khadijah; Andriani Marshanda Lubis; Dian Ayu Puspita Sari; Nurmala Siregar; Nursyamsiah Simbolon; ririn Marheni Br Barus (BADAN PENERBIT STIEPARI PRESS, 2024)
At this time the traditional game of engklek is no longer known and developed in the community, this incident can be triggered by several factors such as the existence of games which are available on cellphones which can result in most children today not being aware of the traditional game of engklek. This research is motivated by the important aim of knowing the existence of the traditional engklek game so that it can improve motor skills that will develop in the child’s body, but not only that, there are also cognitive, language and artistic aspects contained in it. The engklek game is an old game or what is called an ancient game in Indonesia which originates from the Dutch period. Most respondents stated that this game was based on England. This game is also known as “Throwing Stones” or “Gacok” (Yulita, 2017). There are several explanations for the aspects of this game, such as jumping in children can show aspects of gross motor skills. Then children can do different jumps. However, children’s language comprehension can be observed when they actively participate in games, especially if they consist of several groups. When a child is shown the shape of the image in the traditional engklek game which is geometric in shape consisting of a circle, rectangle and square, their cognitive understanding can be observed. From this, young children or AUD will learn that geometry has many different shapes by playing this game. All of this is the child’s understanding that they cannot live their lives without other people, but all problems must be resolved responsibly. Therefore, this research was carried out through observation methods which were carried out by applying various qualitative approach techniques, including those related to research and development.